Studies on The Grasses of Bhagalpur District (Bihar) - Paul, S. R. (Indian Forester, 1967)
The habit, habitat and flowering duration of the grass-flora of Bhagalpur district (Lat. 24Â° 33’ and 26Â° 34’N and Long. 86Â° 19’ and 87Â° 31’ E) has been given. Altogether 45 genera and 81 species have been collected. Only 16 genera belong to sub-family Pooideae, while 29 genera are from the sub-family Panicoideae. Most of the genera of Panicoidese are from tribes Andropogonese and Paniceae, while from Pooldeae the tribes Eragrosteae and Chloridese has more than one genera. Tribe Maydeae is only represented by a single cultivated genus. Majority of the genera are from moist habitats and annuals.